LFP-guided targeting of a cortical barrel column for in vivo two-photon calcium imaging - Lee, Joon-Hyuk; Shin, Hee-Sup; Lee, Kwang-Hyung; Chung, Sooyoung (NATURE PUBLISHING GROUP, 2015)
Two-photon microscopy of bulk-loaded functional dyes is an outstanding physiological technique that enables simultaneous functional mapping of hundreds of brain cells in vivo at single-cell resolution. However, precise targeting of a specific cortical location is not easy due to its fine dimensionality. To enable precise targeting, intrinsic-signal optical imaging is often additionally performed. However, the intrinsic-signal optical imaging is not only time-consuming but also ineffective in ensuring precision. Here, we propose an alternative method for precise targeting based on local field potential (LFP) recording, a conventional electrophysiological method. The heart of this method lies in use of the same glass pipette to record LFPs and to eject calcium dye. After confirming the target area by LFP using a glass pipette, the calcium dye is ejected from the same pipette without a time delay or spatial adjustment. As a result, the calcium dye is loaded into the same ensemble of brain cells from which the LFP was obtained. As a validation of the proposed LFP-based method, we targeted and successfully loaded calcium dye into layer 2/3 of a mouse barrel column.
Keywords: PRIMARY SOMATOSENSORY CORTEX; MOUSE VISUAL-CORTEX; RECEPTIVE-FIELDS; RESPONSE PROPERTIES; PYRAMIDAL CELLS; SENSORY CORTEX; SINGLE NEURONS; REPRESENTATION; ORIENTATION; MICE